THE RESPONSIBILITY OF THE SURABAYA CITY GOVERNMENT TOWARDS PEOPLE WITH MENTAL DISORDERS - Fraja, St. Ika Noerwulan (Faculty of Law Universitas Trunojoyo Madura, 2020)
The local government is one of the parties responsible for the efforts to cure people with mental disorders. Healing efforts are carried out by health workers and must continue to respect the rights of people with mental disorders and provide good health service facilities. Besides having the right to receive treatment and care, they also have the right to receive rehabilitation, even if they do not have a family or a caregiver. The research problem in this study is about the authority of local government towards people with mental disorders. The purpose of this study was to analyze the authority of local governments towards people with mental disorders and the obstacles they face. This research is a legal research with primary, secondary, and tertiary legal materials that are collected using the literature study method and analyzed by the prescriptive method. The authority of the regional government to regulate it is intended to fulfill the rights of people with mental disorders in terms of health services and adequate facilities. even if the person with mental disorders does not have a family or a caregiver.